Hexagonal boron nitride high-temperature-resistant anticorrosive coating system and preparation method thereof
By using a composite coating system with silicone primer and powder melt topcoat in high-temperature resistant coating and performing a "secondary curing" process under high-temperature conditions, the existing coating has been solved in the complex construction process, low durability, and inability to have both mechanical properties, heat resistance and corrosion resistance, and high adhesion, high wear resistance and excellent high temperature and corrosion resistance.
Patent Information
- Application Number
- CN202411673789.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-04
AI Technical Summary
The existing high-temperature resistant coatings have complex construction technology, low durability, and are unable to have both mechanical properties, heat resistance and corrosion resistance.
A composite coating system with silicone primer and powder melted topcoat is adopted. By performing the "secondary curing" process under high temperature conditions, the powder coating forms a vitrified and ceramicized topcoat, improving the adhesion, wear resistance and corrosion resistance of the coating.
It realizes the high adhesion and wear resistance of the coating, excellent high temperature and corrosion resistance, simplifies the construction process, reduces the preparation cost, and improves the overall protective performance of the coating.
Smart Images

Figure CN119752319A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high temperature resistant anticorrosion coatings, and specifically relates to a hexagonal boron nitride high temperature resistant anticorrosion coating system and a preparation method thereof. Background Art
[0002] High temperature resistant coatings are widely used in steam pipes, radiators, thermal power plant boilers, waste incinerators and other scenarios. They not only protect high temperature equipment and reduce the maintenance and replacement frequency of equipment, but also effectively reduce heat loss and energy consumption, thereby reducing material waste and waste emissions in industrial production processes, and then reducing greenhouse gas emissions, which plays a mitigating and positive role in environmental protection and climate change. In the process of actual application, high temperature resistant coatings are also faced with complex construction processes, many restrictions, low coating durability, and inability to combine mechanical properties, heat resistance and corrosion resistance. Organic coatings usually have excellent mechanical properties and corrosion resistance, but are easily oxidized and decomposed under high temperature conditions, resulting in a rapid decrease in protective performance. Inorganic coatings have higher resistance to high temperature oxidation, but their mechanical properties such as flexibility and adhesion are usually not very good, which makes them unable to provide good protection for equipment under many actual working conditions. How to combine organic coatings with inorganic coatings and give full play to the advantages of both is an important issue that needs to be solved in the field of high temperature resistant coatings.
[0003] In order to solve the above problems, it is urgent to develop a new coating system that meets the requirements of high temperature resistance, corrosion resistance and long life. Hexagonal boron nitride, as a two-dimensional nanomaterial, has excellent properties such as high thermal conductivity, high insulation, and high chemical inertness. Adding hexagonal boron nitride to high temperature resistant coatings can not only improve the corrosion resistance and thermal shock resistance of the coating, but also improve the wear resistance of the coating. Therefore, hexagonal boron nitride has broad application prospects in the field of high temperature resistant coatings. Summary of the invention
[0004] The purpose of the present invention is to provide an organic-inorganic composite high-temperature resistant anti-corrosion coating system with high adhesion, high wear resistance, excellent high-temperature resistance and corrosion resistance. To this end, the present invention also provides a preparation method of the anti-corrosion coating system.
[0005] The technical solution adopted by the present invention to solve the technical problem is as follows:
[0006] The invention provides a high temperature resistant anticorrosive coating system, which comprises an organic silicon primer and a powder melting topcoat.
[0007] The mass fraction of the organosilicon primer components is: 60-80 parts of organosilicon resin, 15-20 parts of aminosilane, 2-5 parts of anhydrous ethanol, 2-5 parts of xylene, 0.5-2.5 parts of thixotropic agent, and 0.5-2.5 parts of leveling agent;
[0008] The mass fraction of the powder melting topcoat components is: 35% to 53% petroleum aromatic resin; 35% to 53% low melting point glass powder; 2.5% to 5% (zy) alumina powder; 2.5% to 5% aluminum tripolyphosphate; 1% to 2% hollow glass microspheres; 1% to 2% titanium dioxide; 0.5% to 1% graphite powder; 0.5% to 1% hexagonal boron nitride;
[0009] In addition, before the powder melting topcoat is melted at high temperature (secondary curing), a thin coating of silane hydrolyzate can be used to temporarily fix the powder coating to achieve a better coating appearance and protective effect.
[0010] The mass fractions of the silane hydrolyzate components are: aminosilane 0% to 7.5%; tetraethoxysilane 0% to 2.5%; deionized water 5% to 10%; and anhydrous ethanol 80% to 90%.
[0011] Another object of the present invention is to provide a method for preparing the above coating system, characterized in that the steps are as follows:
[0012] Step 1: Add aromatic resin into a container, refine the petroleum aromatic resin by sand milling, ball milling, stirring milling or stirring shearing, and filter with a 10-60 mesh sieve to obtain refined aromatic resin powder.
[0013] Step 2: Mix the refined aromatic resin powder, low melting point glass powder, alumina powder, aluminum tripolyphosphate powder, hollow glass microspheres, titanium dioxide, graphite powder, and hexagonal boron nitride powder, and continuously shear and stir at a speed of 300 to 600 r / min at room temperature for 0.5 to 2 hours, and finally filter through a 100 to 150 mesh sieve to obtain a uniformly mixed refined powder coating for standby use;
[0014] Step 3: Mix the silicone resin, xylene, thixotropic agent and leveling agent, and stir them continuously at a speed of 300 to 600 r / min for 0.5 to 2 hours at room temperature to obtain a primer base material;
[0015] Step 4: adding aminosilane and anhydrous ethanol to the primer base material solution, and continuously stirring at a speed of 300 to 600 r / min at room temperature for 0.5 to 1 hour to obtain a primer coating;
[0016] Step 5: Apply the primer coating on the surface of the sample by roller coating, brush coating, spray coating or dipping coating to obtain an organic silicone primer with a coating thickness of 80 to 150 μm;
[0017] Step 6: Add the powder coating to the fluidized bed, and set the fluidizing gas pressure range to 0.3-0.5MPa, so that the powder coating reaches a stable fluidized state. Dry the primer-coated sample at room temperature for 10-30 minutes, and then immediately immerse the sample in the fluidized powder coating for 10-30 seconds, take it out, and place it in a ventilated environment at room temperature to dry for 12-36 hours;
[0018] Step 7: Add aminosilane, tetraethoxysilane and anhydrous ethanol to deionized water, and stir continuously at room temperature at a speed of 300 to 600 r / min for 0.5 to 2 hours to obtain a silane hydrolyzate for standby use;
[0019] Step 8: Spray the above-mentioned silane hydrolyzate onto the surface of the sample coated with the two layers of coating, and then place the sample in a ventilated environment at room temperature for drying and curing for 24 to 72 hours. Finally, increase the temperature from room temperature to 400 to 600°C at a heating rate of 5 to 15°C / min, and maintain it at 400 to 600±10°C for 2 to 8 hours to obtain a high temperature resistant anti-corrosion coating.
[0020] In step (1) of the present invention, the aromatic hydrocarbon resin includes, but is not limited to, one or a mixture of C5 aliphatic petroleum resin, C9 aromatic hydrocarbon petroleum resin, DCPD cycloaliphatic diene resin, hydrogenated petroleum resin, and condensed polynuclear aromatic hydrocarbon resin.
[0021] In step (1) of the present invention, the aromatic resin can be refined by a dry method or a wet method. The wet method can use polar solvents with low solubility of aromatic resin such as anhydrous ethanol, methanol, acetone, etc. After the aromatic resin particles are refined, they are dried and ground to obtain high-yield aromatic resin powder.
[0022] In step (2) of the present invention, the softening point of the low-melting-point glass powder is 300-600°C, preferably a mixed low-melting-point glass powder with different softening points in the range of 350-450°C.
[0023] In step (2) of the present invention, the alumina powder is selected from spherical powders with a diameter ranging from 2 to 50 μm, and the preferred powder diameter is 5 to 25 μm.
[0024] In step (2) of the present invention, the hollow glass microspheres are selected from glass microspheres with a wall thickness of 1 to 3 μm and a diameter of 10 to 100 μm, and preferably the wall thickness of the microspheres is 1.5 to 2.5 μm and the diameter is 10 to 35 μm.
[0025] In step (2) of the present invention, the titanium dioxide is rutile titanium dioxide with a particle size of 100 to 400 nm.
[0026] In step (3) of the present invention, the organic silicone resin is an organic silicone resin modified by one or a combination of methyl, ethyl, aromatic and epoxy groups.
[0027] In step (3) of the present invention, the thixotropic agent is one or a combination of organic bentonite, sodium bentonite, lithium bentonite, and fumed silica.
[0028] In step (3) of the present invention, the leveling agent is one or a combination of polydimethylsiloxane, polyether polyester modified organic siloxane, alkyl modified organic siloxane, and acrylate.
[0029] In step (4) of the present invention, the aminosilane is γ-aminopropyltriethoxysilane, and its addition amount is 20% to 40% of the silicone resin base material, preferably 25% to 35%.
[0030] In step (4) of the present invention, in order to ensure that the primer coating remains in a stable undried and cured state within 1 hour of coating, the amount of anhydrous ethanol added is 2% to 10%, preferably 5% to 7%, of the silicone resin base material.
[0031] In step (4) of the present invention, in order to ensure rapid film formation of the coating and maintain good mechanical properties after "secondary curing", the amount of curing agent should be 22.5% to 30% of the base material, preferably 25% to 27.5%.
[0032] In step (5) of the present invention, the coating thickness of the silicone primer is affected by factors such as the coating method and the stirring time of the primer coating, and multiple coats can be applied to ensure that the primer thickness is greater than 80 μm and less than 150 μm.
[0033] In step (6) of the present invention, in order to ensure that the powder coating adheres evenly to the silicone primer, the continuity of the primer coating and the powder coating coating should be ensured, and the powder coating should be applied more than 10 minutes and less than 1 hour after the primer coating is completed. Preferably, the powder coating should be applied when the primer is dry for 15 to 30 minutes.
[0034] In step (7) of the present invention, the aminosilane is γ-aminopropyltriethoxysilane. To ensure the stability of the silane hydrolyzate, the added amount of γ-aminopropyltriethoxysilane is 0% to 7.5% of the total mass of the hydrolyzate, preferably 2.5% to 5%.
[0035] In step (8) of the present invention, in order to ensure that the powder coating melts to form a uniform coating during the "secondary curing" process, the coating surface should be kept in a horizontal state or continuously flipped during the process of heating and maintaining the high temperature of the sample to avoid uneven coating of the surface coating due to powder melting.
[0036] The invention proposes a hexagonal boron nitride high temperature resistant anti-corrosion coating system with good corrosion resistance, excellent adhesion and high temperature resistance. The coating system comprises a silicone primer and a powder melting topcoat, and the coating system thickness is about 100 to 150 μm. The powder coating melts and "secondarily solidifies" under high temperature conditions to form a vitrified and ceramic topcoat. The double-layer coating system exhibits excellent high temperature resistance, corrosion resistance and wear resistance under high temperature conditions.
[0037] The inventors have found through experiments that the durability of silicone resin coating applied alone in high temperature environment is poor. As the service time increases, the silicone coating continues to deteriorate, the mechanical properties drop significantly, and it is easy to crack and desorb when subjected to external impact or friction, thus causing protection failure. Applying low-melting-point glass powder coating alone requires special technology, faces high construction process requirements, and is easy to desorb during service.
[0038] According to the above steps, combining the silicone coating with the improved low-melting-point glass powder coating can reduce the construction process requirements and improve the comprehensive protective performance of the high-temperature resistant coating system.
[0039] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in:
[0040] Low-melting-point glass powder and petroleum resin coating are creatively adhered to the surface of the silicone resin coating, and then a high-temperature "secondary curing" process is used to convert the powder coating into a ceramic coating, so that the silicone primer and the powder melting topcoat form a good combination, and ultimately the coating system exhibits comprehensive high-temperature protection performance. The specific advantages of this coating system are as follows: (1) Silicone resin has good adhesion to the interfaces of different materials such as metal, ceramic, glass, etc. Using silicone as a primer can ensure good adhesion and a wide range of applications of the coating system; (2) The powder melt topcoat combines aromatic resin with low-melting-point glass powder, so that the powder maintains a stable molten flow state during the heating process and gradually transforms into a glass and ceramic structure. It can even be directly put into actual high-temperature working conditions to form a "secondary cure" during the application process without the need for an independent high-temperature curing process; (3) The powder coating is adhered when the base coating is not dried and cured, and there is no need to apply voltage or high temperature to the sample. The construction process is simple, and the amount of powder coating is reduced, thereby reducing the preparation cost; (4) The powder melt coating can not only form air isolation protection for the primer, but also greatly reduce the friction coefficient of the coating surface, thereby improving the wear resistance of the coating system; (5) The addition of hexagonal boron nitride to the powder melt coating can further improve the coating's high temperature resistance, corrosion resistance and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of the structure of the hexagonal boron nitride high temperature resistant anti-corrosion coating system. DETAILED DESCRIPTION
[0042] Example 1
[0043] The anticorrosion coating formula of the present invention is as follows:
[0044] Formula of silicone primer: 70kg of aromatic modified silicone resin, 3kg of anhydrous ethanol, 3kg of xylene, 2kg of organic bentonite, 2kg of polydimethylsiloxane, and 20kg of γ-aminopropyltriethoxysilane.
[0045] Powder topcoat formula: 42.5kg C9 aromatic petroleum resin, 42.5kg mixed low-melting point glass powder, 5kg alumina powder, 5kg aluminum tripolyphosphate powder, 1.5kg hollow glass microspheres, 1.5kg titanium dioxide, 1kg graphite powder, and 1kg hexagonal boron nitride powder.
[0046] Silane hydrolyzate formula: 2.5 kg of γ-aminopropyltriethylsilane, 2.5 kg of tetraethoxysilane, 5 kg of deionized water, and 90 kg of anhydrous ethanol.
[0047] The preparation method of the anticorrosion coating of the present invention:
[0048] 100kg of C9 aromatic petroleum resin is added to a double-layer mixing barrel, a shearing blade is installed on the mixer, water is passed through the mixing barrel to cool it down, the barrel wall temperature is kept below 50°C, and the resin is continuously stirred at a speed of 360r / min for 2 hours to obtain a coarse resin powder. The coarse resin powder is taken out, and the coarse resin powder is sieved with a 50-mesh sieve to obtain a refined resin powder. 42.5kg of the refined resin powder, 42.5kg of mixed low-melting-point glass powder, 5kg of alumina powder, 5kg of aluminum tripolyphosphate powder, 1.5kg of hollow glass microspheres, 1.5kg of titanium dioxide, 1kg of graphite powder, and 1kg of hexagonal boron nitride powder are added to a double-layer mixing barrel, water is passed through the mixing barrel to cool it down, the barrel wall temperature is kept below 50°C, and the resin is continuously stirred at a speed of 360r / min for 1 hour, and finally filtered with a 100-mesh sieve to obtain a uniformly mixed and refined powder coating for standby use.
[0049] 70 kg of aromatic modified silicone resin, 3 kg of xylene, 2 kg of organic bentonite and 2 kg of polydimethylsiloxane were mixed and added into a container, and stirred continuously at 500 r / min for 0.5 hours at room temperature to obtain a primer base material. 20 kg of γ-aminopropyl triethylsilane and 3 kg of anhydrous ethanol were added into the primer base material solution, and stirred continuously at 300 r / min for 1 hour at room temperature to obtain a primer coating. The primer coating was applied on the surface of the sample by brushing to obtain a silicone primer.
[0050] The powder coating is added to the fluidized bed, and the fluidizing gas pressure is set to 0.4MPa, so that the powder coating reaches a stable fluidized state. The sample coated with the primer is placed at room temperature for 15 minutes, and then the sample is immediately immersed in the fluidized powder coating for 15 seconds and taken out, and placed in a room temperature ventilation environment for 36 hours to obtain a specimen coated with silicone primer and powder topcoat. 2.5kg of γ-aminopropyltriethylsilane, 2.5kg of tetraethoxysilane, 5kg of deionized water, and 90kg of anhydrous ethanol are added to the container, and stirred at a speed of 300r / min for 0.5 hours at room temperature to obtain a silane hydrolyzate. The silane hydrolyzate is sprayed onto the surface of the specimen coated with two layers of coating, and then the specimen is placed in a room temperature ventilation environment for drying and curing for 24 hours. Finally, the specimen is placed in a muffle furnace, and the temperature is increased from room temperature to 600℃ at a heating rate of 5℃ / min, and maintained at 600±10℃ for 2 hours and then cooled to room temperature to obtain a high temperature resistant anticorrosion coating.
[0051] Example 1-1
[0052] The aromatic resin in the powder topcoat formula is C5 petroleum resin, and the amount used is 42.5 kg. The rest is consistent with Example 1, and the coating is prepared using the same steps and parameters.
[0053] Example 1-2
[0054] The aromatic hydrocarbon resin in the powder topcoat formula is dicyclopentadiene petroleum resin, and the amount used is 42.5 kg. The rest is consistent with Example 1, and the coating is prepared using the same steps and parameters.
[0055] Examples 1-3
[0056] The powder topcoat formula does not use mixed low-melting-point glass powder, the aromatic resin is C9 petroleum resin, and its dosage is increased to 85 kg. The rest is consistent with Example 1, and the coating is prepared using the same steps and parameters.
[0057] Examples 1-4
[0058] The aromatic hydrocarbon resin is not used in the powder topcoat formula, the amount of the mixed low-melting-point glass powder is increased to 85 kg, and the rest is consistent with Example 1, and the coating is prepared using the same steps and parameters.
[0059] Example 2
[0060] The anticorrosion coating formula of the present invention is as follows:
[0061] Formula of silicone primer: 60kg of aromatic modified silicone resin, 5kg of anhydrous ethanol, 5kg of xylene, 1.5kg of organic bentonite, 2.5kg of polydimethylsiloxane, and 15kg of γ-aminopropyltriethoxysilane.
[0062] Powder topcoat formula: 50kg C9 aromatic petroleum resin, 40kg mixed low-melting point glass powder, 3kg alumina powder, 3kg aluminum tripolyphosphate powder, 1kg hollow glass microspheres, 1kg titanium dioxide, 1kg graphite powder, and 1kg hexagonal boron nitride powder.
[0063] Silane hydrolyzate formula: 2kg of γ-aminopropyltriethylsilane, 5kg of tetraethoxysilane, 5kg of deionized water, and 88kg of anhydrous ethanol.
[0064] The preparation method of the anticorrosion coating of the present invention:
[0065] Add 100kg of C9 aromatic petroleum resin to a double-layer mixing barrel, install a shearing blade on the mixer, cool the mixing barrel with water, keep the barrel wall temperature below 50℃, and stir the resin at a speed of 400r / min for 2 hours to obtain a coarse resin powder. Take out the coarse resin powder, sieve the coarse resin powder with a 40-mesh sieve to obtain a refined resin powder. Take 50kg of the refined resin powder, 40kg of mixed low-melting-point glass powder, 3kg of alumina powder, 3kg of aluminum tripolyphosphate powder, 1kg of hollow glass microspheres, 1kg of titanium dioxide, 1kg of graphite powder, and 1kg of hexagonal boron nitride powder and add them to a double-layer mixing barrel, cool the mixing barrel with water, keep the barrel wall temperature below 50℃, stir the resin at a speed of 400r / min for 2 hours, and finally filter with a 150-mesh sieve to obtain a uniformly mixed and refined powder coating for standby use.
[0066] 60 kg of aromatic modified silicone resin, 5 kg of xylene, 1.5 kg of organic bentonite and 2.5 kg of polydimethylsiloxane were mixed and added into a container, and stirred continuously at a speed of 500 r / min for 0.5 hours at room temperature to obtain a primer base material. 15 kg of γ-aminopropyl triethylsilane and 5 kg of anhydrous ethanol were added into the primer base material solution, and stirred continuously at a speed of 300 r / min for 0.5 hours at room temperature to obtain a primer coating. The primer coating was applied on the surface of the sample by brushing to obtain a silicone primer.
[0067] The powder coating is added to the fluidized bed, and the fluidizing gas pressure is set to 0.3MPa, so that the powder coating reaches a stable fluidized state. The sample coated with the primer is placed at room temperature for 30 minutes, and then the sample is immediately immersed in the fluidized powder coating for 30 seconds and taken out, and placed in a room temperature and ventilated environment for 12 hours to obtain a specimen coated with a silicone primer and a powder topcoat. 2kg of γ-aminopropyltriethylsilane, 5kg of tetraethoxysilane, 5kg of deionized water, and 88kg of anhydrous ethanol are added to the container, and stirred at a speed of 300r / min for 0.5 hours at room temperature to obtain a silane hydrolyzate. The silane hydrolyzate is sprayed onto the surface of the specimen coated with two layers of coating, and then the specimen is placed in a room temperature and ventilated environment for drying and curing for 24 hours. Finally, the specimen is placed in a muffle furnace, and the temperature is increased from room temperature to 600℃ at a heating rate of 15℃ / min, and maintained at 600±10℃ for 2 hours and then cooled to room temperature to obtain a high temperature resistant anticorrosion coating.
[0068] Example 3
[0069] The anticorrosion coating formula of the present invention is as follows:
[0070] Formula of silicone primer: 68kg of ethyl modified silane resin, 3kg of anhydrous ethanol, 5kg of xylene, 2kg of organic bentonite, 2kg of polydimethylsiloxane, and 15kg of γ-aminopropyltriethoxysilane.
[0071] Powder topcoat formula: 40kg C9 aromatic petroleum resin, 45kg mixed low-melting point glass powder, 5kg alumina powder, 5kg aluminum tripolyphosphate powder, 1.5kg hollow glass microspheres, 1.5kg titanium dioxide, 1kg graphite powder, and 1kg hexagonal boron nitride powder.
[0072] Silane hydrolyzate formula: 4 kg of γ-aminopropyltriethylsilane, 1 kg of tetraethoxysilane, 5 kg of deionized water, and 90 kg of anhydrous ethanol.
[0073] The preparation method of the anticorrosion coating of the present invention:
[0074] Add 100kg of C9 aromatic petroleum resin to a double-layer mixing barrel, install a shearing blade on the mixer, cool the mixing barrel with water, keep the barrel wall temperature below 50℃, and stir the resin at a speed of 500r / min for 1 hour to obtain a coarse resin powder. Take out the coarse resin powder, sieve the coarse resin powder with a 50-mesh sieve to obtain a refined resin powder. Take 40kg of the refined resin powder, 45kg of mixed low-melting-point glass powder, 5kg of alumina powder, 5kg of aluminum tripolyphosphate powder, 1.5kg of hollow glass microspheres, 1.5kg of titanium dioxide, 1kg of graphite powder, and 1kg of hexagonal boron nitride powder and add them to a double-layer mixing barrel, cool the mixing barrel with water, keep the barrel wall temperature below 50℃, stir the resin at a speed of 500r / min for 1 hour, and finally filter with a 100-mesh sieve to obtain a uniformly mixed and refined powder coating for standby use.
[0075] 68kg of ethyl modified silicone resin, 5kg of xylene, 2kg of organic bentonite and 2kg of polydimethylsiloxane were mixed and added into a container, and stirred continuously at 500r / min for 0.5 hours at room temperature to obtain a primer base material. 15kg of γ-aminopropyl triethylsilane and 3kg of anhydrous ethanol were added into the primer base material solution, and stirred continuously at 300r / min for 0.5 hours at room temperature to obtain a primer coating. The primer coating was sprayed on the surface of the sample, and another spray was applied 0.5 hours after the first spray was completed to obtain a silicone primer.
[0076] The powder coating is added to the fluidized bed, and the fluidizing gas pressure is set to 0.4MPa, so that the powder coating reaches a stable fluidized state. The sample coated with the primer is placed at room temperature for 15 minutes, and then the sample is immediately immersed in the fluidized powder coating for 15 seconds and taken out, and placed in a room temperature ventilation environment for 12 hours to obtain a specimen coated with a silicone primer and a powder topcoat. 4kg of γ-aminopropyltriethylsilane, 1kg of tetraethoxysilane, 5kg of deionized water, and 90kg of anhydrous ethanol are added to the container, and stirred continuously at room temperature at a speed of 300r / min for 0.5 hours to obtain a silane hydrolyzate. The silane hydrolyzate is sprayed onto the surface of the specimen coated with two layers of coating, and then the specimen is placed in a room temperature ventilation environment for drying and curing for 24 hours. Finally, the specimen is placed in a muffle furnace, and the temperature is increased from room temperature to 400℃ at a heating rate of 10℃ / min, and maintained at 400±10℃ for 2 hours and then cooled to room temperature to obtain a high temperature resistant anticorrosion coating.
[0077] Example 4
[0078] The anticorrosion coating formula of the present invention is as follows:
[0079] Silicone primer formula: 70kg of silicone-modified epoxy resin, 3kg of anhydrous ethanol, 3kg of xylene, 2kg of calcium-based bentonite, 2kg of polydimethylsiloxane, and 20kg of γ-aminopropyltriethoxysilane.
[0080] Powder topcoat formula: 35kg C9 aromatic petroleum resin, 50kg mixed low-melting point glass powder, 5kg alumina powder, 5kg aluminum tripolyphosphate powder, 1kg hollow glass microspheres, 2kg titanium dioxide, 1kg graphite powder, and 1kg hexagonal boron nitride powder.
[0081] Silane hydrolyzate formula: 5kg of γ-aminopropyltriethylsilane, 5kg of deionized water, and 90kg of anhydrous ethanol.
[0082] The preparation method of the anticorrosion coating of the present invention:
[0083] Add 100kg of C9 aromatic petroleum resin to a double-layer mixing barrel, install a shearing blade on the mixer, cool the mixing barrel with water, keep the barrel wall temperature below 50℃, and stir the resin at a speed of 600r / min for 1.5 hours to obtain a coarse resin powder. Take out the coarse resin powder, sieve the coarse resin powder with a 50-mesh sieve to obtain a refined resin powder. Take 35kg of the refined resin powder, 50kg of mixed low-melting-point glass powder, 5kg of alumina powder, 5kg of aluminum tripolyphosphate powder, 1kg of hollow glass microspheres, 2kg of titanium dioxide, 1kg of graphite powder, and 1kg of hexagonal boron nitride powder and add them to a double-layer mixing barrel, cool the mixing barrel with water, keep the barrel wall temperature below 50℃, stir the resin at a speed of 600r / min for 1 hour, and finally filter with a 120-mesh sieve to obtain a uniformly mixed and refined powder coating for standby use.
[0084] 70 kg of organosilicon-modified epoxy resin, 3 kg of xylene, 2 kg of calcium-based bentonite, and 2 kg of polydimethylsiloxane were mixed and added to a container, and stirred at a speed of 500 r / min for 0.5 hours at room temperature to obtain a primer base material. 20 kg of γ-aminopropyl triethyl silane and 3 kg of anhydrous ethanol were added to the above primer base material solution, and stirred at a speed of 300 r / min for 1 hour at room temperature to obtain a primer coating. The above primer coating was applied to the surface of the sample by brushing to obtain an organosilicon primer.
[0085] The powder coating is added to the fluidized bed, and the fluidizing gas pressure is set to 0.3MPa, so that the powder coating reaches a stable fluidized state. The sample coated with the primer is placed at room temperature for 25 minutes, and then the sample is immediately immersed in the fluidized powder coating for 15 seconds and taken out, and placed in a room temperature and ventilated environment for 24 hours to obtain a test piece coated with silicone primer and powder topcoat. 5kg of γ-aminopropyltriethylsilane, 5kg of deionized water, and 90kg of anhydrous ethanol are added to the container, and stirred at a speed of 300r / min for 0.5 hours at room temperature to obtain a silane hydrolyzate. The silane hydrolyzate is sprayed onto the surface of the test piece coated with two layers of coating, and then the test piece is placed in a room temperature and ventilated environment for drying and curing for 24 hours. Finally, the test piece is placed in a muffle furnace, and the temperature is increased from room temperature to 400℃ at a heating rate of 15℃ / min, and kept at 400±10℃ for 2 hours and then cooled to room temperature to obtain a high temperature resistant anticorrosion coating.
[0086] Example 5
[0087] The anticorrosion coating formula of the present invention is as follows:
[0088] Silicone primer formula: 64kg of silicone-modified epoxy resin, 5kg of anhydrous ethanol, 5kg of xylene, 2kg of calcium-based bentonite, 2kg of polydimethylsiloxane, and 16kg of γ-aminopropyltriethoxysilane.
[0089] Powder topcoat formula: 35kg C9 aromatic petroleum resin, 50kg mixed low-melting point glass powder, 5kg alumina powder, 5kg aluminum tripolyphosphate powder, 1kg hollow glass microspheres, 2kg titanium dioxide, 1kg graphite powder, and 1kg hexagonal boron nitride powder.
[0090] The preparation method of the anticorrosion coating of the present invention:
[0091] Add 100kg of C9 aromatic petroleum resin to a double-layer mixing barrel, install a shearing blade on the mixer, cool the mixing barrel with water, keep the barrel wall temperature below 50℃, and stir the resin at a speed of 500r / min for 2 hours to obtain a coarse resin powder. Take out the coarse resin powder, sieve the coarse resin powder with a 50-mesh sieve to obtain a refined resin powder. Take 35kg of the refined resin powder, 50kg of mixed low-melting-point glass powder, 5kg of alumina powder, 5kg of aluminum tripolyphosphate powder, 1kg of hollow glass microspheres, 2kg of titanium dioxide, 1kg of graphite powder, and 1kg of hexagonal boron nitride powder and add them to a double-layer mixing barrel, cool the mixing barrel with water, keep the barrel wall temperature below 50℃, stir the resin at a speed of 500r / min for 1 hour, and finally filter with a 150-mesh sieve to obtain a uniformly mixed and refined powder coating for standby use.
[0092] 64 kg of organosilicon-modified epoxy resin, 5 kg of xylene, 2 kg of calcium-based bentonite, and 2 kg of polydimethylsiloxane were mixed and added to a container, and stirred at a speed of 500 r / min for 0.5 hours at room temperature to obtain a primer base material. 16 kg of γ-aminopropyl triethylsilane and 5 kg of anhydrous ethanol were added to the above-mentioned primer base material solution, and stirred at a speed of 300 r / min for 1 hour at room temperature to obtain a primer coating. The above-mentioned primer coating was applied to the surface of the sample by brushing to obtain an organosilicon primer.
[0093] The powder coating is added to the fluidized bed, and the fluidizing gas pressure is set to 0.3MPa, so that the powder coating reaches a stable fluidized state. The primer-coated sample is placed at room temperature for 25 minutes, and then immediately immersed in the fluidized powder coating for 15 seconds, taken out, and placed in a room temperature and ventilated environment for 24 hours to obtain a specimen coated with silicone primer and powder topcoat. Finally, the specimen is placed in a muffle furnace, and the temperature is increased from room temperature to 500°C at a heating rate of 5°C / min, and maintained at 500±10°C for 2 hours and then cooled to room temperature to obtain a high temperature resistant anti-corrosion coating.
[0094] Comparative Example 1
[0095] Comparative Example 1: A powder topcoat component and an organosilicon primer component were mixed to prepare a coating layer.
[0096] Paint formula: 64kg silicone epoxy resin, 5kg anhydrous ethanol, 5kg xylene, 2kg organic bentonite, 2kg polydimethylsiloxane, 16kg γ-aminopropyltriethoxysilane, 8kg C9 aromatic petroleum resin, 8kg mixed low-melting point glass powder, 1kg alumina powder, 1kg aluminum tripolyphosphate powder, 0.3kg hollow glass microspheres, 0.3kg titanium dioxide, 0.2kg graphite powder, 0.2kg hexagonal boron nitride powder.
[0097] The preparation method of the anticorrosion coating of the present invention:
[0098] 100kg of C9 aromatic petroleum resin is added to a double-layer mixing barrel, a shearing blade is installed on the mixer, water is passed through the mixing barrel to cool it down, the barrel wall temperature is kept below 50°C, and the resin is continuously stirred at a speed of 360r / min for 2 hours to obtain a coarse resin powder. The coarse resin powder is taken out, and the coarse resin powder is sieved with a 50-mesh sieve to obtain a refined resin powder. 42.5kg of the refined resin powder, 42.5kg of mixed low-melting-point glass powder, 5kg of alumina powder, 5kg of aluminum tripolyphosphate powder, 1.5kg of hollow glass microspheres, 1.5kg of titanium dioxide, 1kg of graphite powder, and 1kg of hexagonal boron nitride powder are added to a double-layer mixing barrel, water is passed through the mixing barrel to cool it down, the barrel wall temperature is kept below 50°C, and the resin is continuously stirred at a speed of 360r / min for 1 hour, and finally filtered with a 100-mesh sieve to obtain a uniformly mixed and refined powder coating for standby use.
[0099] 64kg of silicone epoxy resin, 5kg of anhydrous ethanol, 5kg of xylene, 2kg of organic bentonite and 2kg of polydimethylsiloxane were mixed and added to the container, and then 8kg of the above-mentioned refined powder coating was added to the silicone resin base material solution, and stirred at a speed of 500r / min for 0.5 hours at room temperature to obtain a primer base material. 16kg of γ-aminopropyltriethylsilane and 3kg of anhydrous ethanol were added to the above-mentioned silicone resin base material solution, and stirred at a speed of 300r / min for 1 hour at room temperature to obtain a coating solution. The above-mentioned coating was applied to the surface of the sample by brushing to obtain a silicone coating specimen. Finally, the specimen was placed in a muffle furnace, and the temperature was increased from room temperature to 600℃ at a heating rate of 5℃ / min, and kept at 600±10℃ for 2 hours and then cooled to room temperature to obtain a high temperature resistant anti-corrosion coating.
[0100] Comparative Example 2
[0101] Comparative Example 2: The powder coating component is added to the silane hydrolyzate and sprayed onto the surface of the primer to form a topcoat.
[0102] Formula of silicone primer: 70kg of aromatic modified silicone resin, 3kg of anhydrous ethanol, 3kg of xylene, 2kg of organic bentonite, 2kg of polydimethylsiloxane, and 20kg of γ-aminopropyltriethoxysilane.
[0103] Topcoat formula: 4kg C9 aromatic petroleum resin, 4.5kg mixed low-melting point glass powder, 0.5kg alumina powder, 0.5kg aluminum tripolyphosphate powder, 0.15kg hollow glass microspheres, 0.15kg titanium dioxide, 0.1kg graphite powder, 0.1kg hexagonal boron nitride powder, 0.25kg γ-aminopropyltriethylsilane, 0.25kg tetraethoxysilane, 0.5kg deionized water, 9kg anhydrous ethanol.
[0104] The preparation method of the anticorrosion coating of the present invention:
[0105] 100kg of C9 aromatic petroleum resin is added to a double-layer mixing barrel, a shearing blade is installed on the mixer, water is passed through the mixing barrel to cool it down, the barrel wall temperature is kept below 50°C, and the resin is continuously stirred at a speed of 360r / min for 2 hours to obtain a coarse resin powder. The coarse resin powder is taken out, and the coarse resin powder is sieved with a 50-mesh sieve to obtain a refined resin powder. 42.5kg of the refined resin powder, 42.5kg of mixed low-melting-point glass powder, 5kg of alumina powder, 5kg of aluminum tripolyphosphate powder, 1.5kg of hollow glass microspheres, 1.5kg of titanium dioxide, 1kg of graphite powder, and 1kg of hexagonal boron nitride powder are added to a double-layer mixing barrel, water is passed through the mixing barrel to cool it down, the barrel wall temperature is kept below 50°C, and the resin is continuously stirred at a speed of 360r / min for 1 hour, and finally filtered with a 100-mesh sieve to obtain a uniformly mixed and refined powder coating for standby use.
[0106] 70 kg of aromatic modified silicone resin, 3 kg of xylene, 2 kg of organic bentonite and 2 kg of polydimethylsiloxane were mixed and added into a container, and stirred continuously at 500 r / min for 0.5 hours at room temperature to obtain a primer base material. 20 kg of γ-aminopropyl triethylsilane and 3 kg of anhydrous ethanol were added into the primer base material solution, and stirred continuously at 300 r / min for 1 hour at room temperature to obtain a primer coating. The primer coating was applied on the surface of the sample by brushing to obtain a silicone primer.
[0107] Take 10kg of the above-mentioned refined coating powder, mix it with 0.25kg of γ-aminopropyltriethylsilane, 0.25kg of tetraethoxysilane, 0.5kg of deionized water and 9kg of anhydrous ethanol, add it to a container, and stir it continuously at a speed of 300r / min at room temperature for 1 hour to obtain a topcoat coating. Spray the topcoat coating on the surface of the sample to obtain a topcoat. Place the above-mentioned double-layer coating specimen in a room temperature and ventilated environment for drying and curing for 24 hours. Finally, place the specimen in a muffle furnace, increase the temperature from room temperature to 600℃ at a heating rate of 5℃ / min, keep it at 600±10℃ for 2 hours and then return it to room temperature to obtain a high temperature resistant anti-corrosion coating.
[0108] The various properties of the new high temperature resistant anti-corrosion coating are shown in Tables 1 and 2 below.
[0109] Table 1 Test results of various properties of the new high temperature resistant anticorrosion coating obtained by the control variable method related to the embodiment
[0110]
[0111]
[0112] Table 2 Test results of various properties of new high temperature resistant anticorrosion coating
[0113]
[0114]
[0115] In summary, through the comparison of the examples and comparative examples in Tables 1 and 2, the powder melt coating can not only improve the mechanical properties of the coating in all aspects, but also significantly improve the heat resistance and corrosion resistance of the coating. The fundamental reason is that the powder adheres to the surface of the silicone coating and forms a ceramic coating by "secondary curing" under high temperature conditions. The ceramic coating fully exerts its high temperature resistance, corrosion resistance and wear resistance, and the protectiveness of the silicone primer in the ceramic topcoat can maintain its excellent mechanical properties. Figure 1 This is a schematic diagram of the formation of the powder melting coating. It can be seen that a smooth ceramic coating is formed on the surface after the powder is melted. The hexagonal boron nitride improves the thermal shock resistance of the coating on the one hand, and also improves the wear resistance of the coating on the other hand.
[0116] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Hexagonal boron nitride high temperature resistant anti-corrosion coating system, characterized in that: The high temperature resistant coating system comprises an organic silicon primer and a powder melting topcoat, and the components of the powder melting topcoat include petroleum aromatic resin and low melting point glass powder.
2. The hexagonal boron nitride high temperature resistant anticorrosion coating system according to claim 1, characterized in that: The mass fractions of the powder melting topcoat components are: 35% to 53% of petroleum aromatic resin; 35% to 53% of low melting point glass powder; 2.5% to 5% of alumina powder; 2.5% to 5% of aluminum tripolyphosphate; 1% to 2% of hollow glass microspheres; 1% to 2% of titanium dioxide; 0.5% to 1% of graphite powder; and 0.5% to 1% of hexagonal boron nitride.
3. The hexagonal boron nitride high temperature resistant anticorrosion coating system according to claim 1 or 2, characterized in that: The mass fractions of the organic silicon primer components are: 60-80 parts of organic silicon resin, 15-20 parts of aminosilane, 2-5 parts of anhydrous ethanol, 2-5 parts of xylene, 0.5-2.5 parts of thixotropic agent and 0.5-2.5 parts of leveling agent.
4. The hexagonal boron nitride high temperature resistant anticorrosion coating system according to claim 1 or 2, characterized in that: The powder molten topcoat is temporarily fixed with a thin coating of silane hydrolyzate before being melted at high temperature for secondary curing.
5. The hexagonal boron nitride high temperature resistant anticorrosion coating system according to claim 4, characterized in that: The mass fractions of the silane hydrolyzate components are: aminosilane 0% to 7.5%; tetraethoxysilane 0% to 2.5%; deionized water 5% to 10%; and anhydrous ethanol 80% to 90%.
6. The method for preparing the high temperature resistant and anticorrosive coating system of hexagonal boron nitride according to claim 1, characterized in that: The method comprises the following steps: Step 1: adding aromatic resin into a container, refining the petroleum aromatic resin by sand milling, ball milling, stirring milling or stirring shearing, and filtering with a 10-60 mesh sieve to obtain refined aromatic resin powder; Step 2: Mix the refined aromatic resin powder, low melting point glass powder, alumina powder, aluminum tripolyphosphate powder, hollow glass microspheres, titanium dioxide, graphite powder, and hexagonal boron nitride powder, and continuously shear and stir at a speed of 300 to 600 r / min at room temperature for 0.5 to 2 hours, and finally filter through a 100 to 150 mesh sieve to obtain a uniformly mixed refined powder coating for standby use; Step 3: Mix the silicone resin, xylene, thixotropic agent and leveling agent, and stir them continuously at a speed of 300 to 600 r / min for 0.5 to 2 hours at room temperature to obtain a primer base material; Step 4: adding aminosilane and anhydrous ethanol to the primer base material solution, and continuously stirring at a speed of 300 to 600 r / min at room temperature for 0.5 to 1 hour to obtain a primer coating; Step 5: Apply the primer coating on the surface of the sample by roller coating, brush coating, spray coating or dipping coating to obtain an organic silicone primer with a coating thickness of 80 to 150 μm; Step 6: Add the powder coating into a fluidized bed, and set the fluidizing gas pressure range to 0.3-0.5 MPa, so that the powder coating reaches a stable fluidized state; place the primer-coated sample at room temperature for drying for 10-30 minutes, and then immediately immerse the sample in the fluidized powder coating for 10-30 seconds, take it out, and place it in a ventilated environment at room temperature for drying for 12-36 hours; Step 7: Add aminosilane, tetraethoxysilane and anhydrous ethanol into deionized water, and stir continuously at room temperature at a speed of 300 to 600 r / min for 0.5 to 2 hours to obtain a silane hydrolyzate for standby use. Step 8: Spray the above-mentioned silane hydrolyzate onto the surface of the sample coated with the two layers of coating, and then place the sample in a ventilated environment at room temperature for drying and curing for 24 to 72 hours, and finally increase the temperature from room temperature to 400 to 600°C at a heating rate of 5 to 15°C / min, and maintain it at 400 to 600±10°C for 2 to 8 hours to obtain a high temperature resistant anti-corrosion coating; 7. The method for preparing the high temperature resistant and anticorrosive coating system of hexagonal boron nitride according to claim 6, characterized in that: The aromatic hydrocarbon resin described in step 1 includes one or a mixed resin of C5 aliphatic petroleum resin, C9 aromatic hydrocarbon petroleum resin, DCPD cycloaliphatic diene resin, hydrogenated petroleum resin, and condensed polynuclear aromatic hydrocarbon resin.
8. The method for preparing the high temperature resistant and anticorrosive coating system of hexagonal boron nitride according to claim 6 or 7, characterized in that: The softening point temperature of the low-melting-point glass powder in step 2 is a mixed low-melting-point glass powder with different softening points in the range of 300 to 600°C.
9. The method for preparing the high temperature resistant and anticorrosive coating system of hexagonal boron nitride according to claim 6 or 7, characterized in that: In step 6, to ensure uniform adhesion of the powder coating on the silicone primer, the continuity of the primer coating and the powder coating coating should be ensured, and the powder coating should be applied more than 10 minutes and less than 1 hour after the primer coating is completed.
10. The method for preparing the high temperature resistant and anticorrosive coating system of hexagonal boron nitride according to claim 6 or 7, characterized in that: In step 8, in order to ensure that the powder coating melts to form a uniform coating during the "secondary curing" process, the coating surface must be kept in a horizontal state or continuously flipped during the process of heating and maintaining the high temperature of the sample to avoid uneven coating on the surface due to powder melting.